Black Box Thinking: The Surprising Truth About Success - and Syed, Matthew (Hachette UK, 2015)
The Sunday Times No.1 Bestseller From the Bestselling Author of BounceWhat links the Mercedes Formula One team with Google?What links Team Sky and the aviation industry?What connects James Dyson and David Beckham?They are all Black Box Thinkers.Black Box Thinking is a new approach to high performance, a means of finding an edge in a complex and fast-changing world. It is not just about sport, but has powerful implications for business and politics, as well as for parents and students. In other words, all of us.Drawing on a dizzying array of case studies and real-world examples, together with cutting-edge research on marginal gains, creativity and grit, Matthew Syed tells the inside story of how success really happens - and how we cannot grow unless we are prepared to learn from our mistakes.
Keywords: Psychology; Sports & Recreation / Sports Psychology; Strategic Planning